The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1007/bf00195093
|View full text |Cite
|
Sign up to set email alerts
|

The spatial modulation of a forced triangular jet

Abstract: An investigation of the possibility of controlling the evolution of jets into the far field is presented. Driven by practical concerns the study examined a highly turbulent jet flow. To enhance controllability of the flow evolution the virtues of non-circular nozzles and active flow excitation were combined. The study examined an air jet, Reae = 8ooo, average turbulence intensity 1.8% issuing into stagnant room air out of a triangular nozzle, which had piezoceramic actuators mounted on the flat sides. The evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…More recently, strong instabilities of a jet column were observed when a square jet was forced using azimuthal modes excitation effected via amplitude modulation, although detailed analysis about the effects of nozzle geometry on the jet dynamics was not provided (Wiltse and Glezer 1993). In later work, spatial mode excitation had been implemented on triangular jets and elliptic jets with various initial velocity profiles (Vandsburger and Ding 1995;Ding 1995). It was shown that the initial velocity profiles have significant influence on the effects of such combined excitations in terms of the flow characteristics associated with nozzle geometry.…”
Section: Mixing Control Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, strong instabilities of a jet column were observed when a square jet was forced using azimuthal modes excitation effected via amplitude modulation, although detailed analysis about the effects of nozzle geometry on the jet dynamics was not provided (Wiltse and Glezer 1993). In later work, spatial mode excitation had been implemented on triangular jets and elliptic jets with various initial velocity profiles (Vandsburger and Ding 1995;Ding 1995). It was shown that the initial velocity profiles have significant influence on the effects of such combined excitations in terms of the flow characteristics associated with nozzle geometry.…”
Section: Mixing Control Methodsmentioning
confidence: 99%
“…(Sforza et al 1966, Trentacoste & Sforza 1967. Later studies of jets emerging from noncircular nozzles with corners showed that the introduction of sharp corners in the nozzle can increase significantly the fine-scale turbulence at the corners relative to the flat segments of the nozzle (Schadow et al 1988, Toyoda & Hussain 1989 and enhance mass entrainment (Vandsburger & Ding 1995). In some cases, the small-scale turbulence was produced by threedimensional flows, which were formed at the corner regions inside the nozzle (Su & Friedrich 1994).…”
Section: Outline Of the Thesismentioning
confidence: 99%
See 1 more Smart Citation
“…The sharp corners lead to the generation of high-frequency turbulent eddies, and the edges shed large-scale coherent structures, thus resulting in higher spread along the edge than that along vertex [9]. The small-and large-scale mixing is essential in combustion systems [10], and to improve the entrainment rate [11]. Further, the triangular jets introduce ''high-instability modes into the flow via the non-symmetric mean velocity and pressure distribution around the nozzle'' as discussed by Schadow et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…One point that is not fully investigated in previous studies is the e¨ect of corner radii in noncircular jets and this point is indicated to be a further research topic by Quinn [4]. The existence of sharp corners in the nozzle can increase the ¦ne-scale turbulence at the corners relative to the §at segments of the nozzle as indicated in [5,6], and enhance mass entrainment signi¦cantly in [7].…”
Section: Introductionmentioning
confidence: 99%